Dupilumab for atopic manifestations in pediatric patients with inborn errors of immunity: efficacy and safety in a genetically diverse cohort - Alsediq, Najla; Algholaiqa, Thekra; Alnami, Ghadah; AlJaber, Abdulrahman N. (Frontiers in Immunology, 2025)
BackgroundInborn Errors of Immunity (IEI) are monogenic disorders that predispose patients to infections, autoimmunity, atopy, and malignancies. Severe Th2-driven atopic dermatitis and asthma are common in several IEIs, including DOCK8 deficiency, STAT3 loss-of-function, and Wiskott–Aldrich syndrome, often refractory to conventional therapies. Dupilumab, a monoclonal antibody targeting IL-4Rα, has shown promise in managing recalcitrant atopic dermatitis and asthma, but data in immunocompromised pediatric populations remain limited.MethodsWe conducted a single-center, retrospective observational cohort study with prospective follow-up of ten pediatric patients with genetically confirmed IEI and atopic manifestations. Patients received subcutaneous dupilumab (300 mg every 4 weeks for atopic dermatitis; every 2 weeks for severe asthma). Outcomes were assessed using the Eczema Area and Severity Index (EASI), Dermatology Life Quality Index (DLQI), Childhood Asthma Control Test (C-ACT), eosinophil counts, and infection frequency across four time points (baseline, 6 months, 12 months, >18 months).ResultsThe cohort included ten patients (6 males, 4 females) with mutations in DOCK8 (n=5), CARD11 (n=2), STAT3 LOF (n=1), ADA (n=1), and PEPD (n=1). Of ten patients, nine received dupilumab for atopic dermatitis. Baseline EASI and DLQI scores were 34.33 and 25.0, respectively. Following dupilumab therapy, mean EASI decreased to 2.67 (p<0.001) and DLQI improved to 2.67 (p<0.001), with sustained response observed over 18 months. Peripheral eosinophil counts declined from 2.0×109/L to 0.45×109/L (p<0.001). One patient with severe asthma achieved C-ACT improvement from 10 to 26 with no subsequent exacerbations. Treatment was well-tolerated, with only mild conjunctivitis or transient hypereosinophilia reported. Notably, skin infections resolved, and no systemic or opportunistic infections were observed.ConclusionDupilumab is a safe and highly effective therapeutic option for pediatric patients with IEI-associated atopic manifestations, improving clinical outcomes, quality of life, and infection profile while preserving immune function. These findings support broader application of dupilumab in patients with IEI and warrant further investigation in larger, multicenter studies.